Majken Bullard COVID-19 Essay - Bullard, Majken::::::::: (2021)
A personal narrative titled "The Unexpected Possibilities of a Pandemic: An Essay" which reflects Majken Bullard's experiences as a student and parent during the COVID-19 pandemic.